Beneficial effects of ellagic acid against animal models of scopolamine- and diazepam-induced cognitive impairments. (2nd October 2016) - Mansouri, Mohammad Taghi; Farbood, Yaghoub; Naghizadeh, Bahareh; Shabani, Sohreh; Mirshekar, Mohammad Ali; Sarkaki, Alireza
Abstract: Context In a previous study, it has been shown that ellagic acid (EA), a polyphenolic compound found in pomegranate and different berries, prevents cognitive and hippocampal long-term potentiation (LTP) impairments induced by traumatic brain injury in rats through antioxidant and anti-inflammatory mechanisms. Objective The present study was conducted to assess the potential of EA as a memory enhancer. Materials and methods The elevated plus maze (EPM) and passive avoidance (PA) paradigm were used to evaluate learning and memory parameters. Three doses (10, 30 and 100 mg/kg, i.p.) of EA were administered to animals. Memory impairment was induced by scopolamine treatment (0.4 mg/kg, i.p.) and/or diazepam (1 mg/kg, i.p.). Acquisition trials were carried out 30 min after scopolamine treatment and retention trials were performed for 5 min 24 h after the acquisition trials. Results EA at doses 30 and 100 mg/kg significantly reversed the amnesia induced by scopolamine (0.4 mg/kg, i.p.) in the EPM and PA tests in mice. Also, EA at doses 30 and 100 mg/kg significantly antagonized the amnesia induced by diazepam (1 mg/kg, i.p.) in EPM test in rats. Moreover, chronic administration of EA at dose 30 mg/kg ameliorated the memory deficit induced by diazepam (1 mg/kg, i.p.) in rats. Discussion and conclusion This study demonstrates that ellagic acid is effective in preventing scopolamine- and diazepam-induced cognitive impairments without altering the animals' locomotion. This suggests the potential of EA application as a useful memory restorative agent in the treatment of dementia seen in elderly persons.